Free movement of workers in European Union and free movement right for Turkish Nationals - Ayhan, Sinan (My University, 2003)
Bu çalışmada Kişilerin Serbest Dolaşımı kavramının Avrupa Birliği hukukuna göre ne anlama geldiği ve bu yasal sürecin Türk vatandaşları açısında doğurduğu sonuçlar ortaya konulmaya çalışılmıştır. Tezin ilk bölümünde Avrupa Birligi Hukukunda kişilerin serbest dolaşımı hakkını ortaya çıkaran temel hukuki belgelere ve bu hakkın pratik uygulanması esnasında ortaya çıkan bazı sorunlara ve bu sorunlara Avrupa Toplulukları Adalet Divanının uygun bulduğu çözümlere yer verilmiştir. İkinci bölümde ise Türkiye ve Avrupa Birligi arasında akdedilen ve hükümleri itibarı ile kişilerin serbest dolaşımı sonucu doğurması muhtemel olan Ankara Antlaşması ve Katma Protokol incelenmiş, özellikle Avrupa Birliği ülkelerinde halihazırda yasal olarak çalışmakta bulunan vatandaşlarımızın haklarının iyileştirilmesine yönelik Ankara Antlaşması uyarınca kurulan Ortaklık Konseyinin aldığı kararlar üzerinde durulmuş ve bu kararlar temel alınarak Türk vatandaşları tarafından Avrupa Toplulukları Adalet Divanınca karara bağlanmış davalara değinilmiştir. Tüm bu süreç genel olarak incelendiğinde Türkiye'nin Ankara Antlaşmasından ve Katma Protokolden kaynaklanan Türk vatandaşlarının serbest dolaşımı ile ilgili henüz gerçekleşmemiş hakları olsa da artık bu durumun iki taraf tarafından da göz ardı edildiği ve 1999 Helsinki Zirvesi sonuç bildirisi ile Türkiye'ye adaylık statüsü verilmesiyle birlikte ortaklık ilişkilerinin yeni bir boyut kazandığı, kişilerin serbest dolaşımı konusunda Avrupa Birliği'nin Türk vatandaşlarına tanıyacağı hakların artık Ankara Antlaşması ve Katma Protokol kaynaklı olmayacağı, adaylık sürecinde müzakere edilmek suretiyle ortaya çıkacağı anlaşılmış bulunmaktadır. This study will examine what Free Movement of Workers means within the European Union Law on one hand and what implications does this concept have on Turkish citizens on the other hand. The first part of this thesis will focus on the legal texts, which constitute the basis of this right and practical application by concentrating on the Cases and Conclusions of the European Court of Justice. In the second part the thesis is more about the situation of Turkish workers who pursues to exercise this right. The EC Treaty defines in Article 48 EC freedom of movement for workers'' as entailing the abolition of any direct or indirect discrimination based on nationality in the case of access to employment, remuneration and other conditions of work and employment. Article 48 provides that: 1)Freedom of movement for workers shall be secured within the Community by the end of the transitional period at the least. Such freedom of movement shall entail the abolition of any discrimination based on nationality between workers of the Member States as regards employment, remuneration and other conditions of work and employment. The application of free movement right is based on Regulation (EEC) No 1612/ 68, which states in its preamble that mobility of labor within the Community must be one of the means by which the worker is guaranteed the possibility of improving his living and working conditions and promoting his social advancement. Second part of the thesis deals with the implications of this right on Turkish Citizens. For the Turkish Citizens, the main legal basis of the freedom for the movement of workers is the Article 12 of the Ankara Treaty.Article 12 states that: The Contracting Parties agree to be guided by Articles 48, 49 and 50 of the Treaty establishing the Community for the purpose of progressively securing freedom of movement for workers between them. Moreover Article 36 of the Additional Protocol states that Freedom of movement for workers between Member States of the Community and Turkey shall be secured by progressive stages in accordance with the principles set out in Article 12 of the Agreement of Association between the end of the twelfth and the twenty-second year after the entry into force of that Agreement. The Council of Association shall decide on the rules necessary to that end. This study will further examine the practical application of these principles laid down by the Decisions of the Associaiton Council established by the Additional Protocol by concentrating of the Cases relating to Turkish Citizens. Last parts of the thesis focus on the recent and future situation in this respect.
Keywords: Avrupa Birliği_Hukuk